Cause of Hispanic homicides in major metropolitan areas - Bisciglia, Michael Gregory (2008)
Research investigating the relationship between segregation and crime has been extensively examined in the literature. Although numerous studies have looked at segregation’s influence homicides, most have focused on African Americans. This study extends current research by focusing on Hispanic segregation and homicide victimization. Using a 236 city sample, homicides are shown to rise when Hispanics are segregated from Whites. In comparison, a 208 city sample finds that segregation also contributes to a rise in African American homicides. It was also expected that the more homogeneous Hispanic population would reduce homicides, but such an association was not present in the full Hispanic model, only in the individual Mexican analysis. This study also goes beyond previous research by using ethnic specific measures to examine homicide. By analyzing homicides on the basis of a specific ethnic group, the findings illustrated that segregation measured as dissimilarity consistently effected homicides for all groups, while segregation measured as exposure shows inconsistent results. This analysis also explores segregation disaggregated by social class. Among Hispanics and African Americans, although segregation increases with social class, its impact on homicide is only significant in the lower class. Changes in segregation from 1980-1990 and 1990-2000 were also expected to have a significant impact on homicides, but contrary to the expectations, only the change in exposure from 1980-1990 is significantly related to homicides for African Americans and Hispanics. Finally this study examines the direct and indirect effect of female-headed households on homicides. For all Hispanics, female-headed households are not associated with homicide, but it is significant for Mexicans specifically. It was also significant for African American